2018
DOI: 10.1016/j.marpolbul.2018.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal concentrations in the muscle of seven marine species: Comparison between the Gulf of Lions (North-West Mediterranean Sea) and the Bay of Biscay (North-East Atlantic Ocean)

Abstract: Concentrations of 6 trace metals (Ag, Cd, Cu, Ni, Pb, Zn) in the muscle of 2 sharks (Galeus melastomus and Scyliorhinus canicula), 4 teleosts (Helicolenus dactylopterus, Lepidorhombus boscii, Micromesistius poutassou and Phycis blennoides) and 1 crustacean (Nephrops norvegicus) were compared between the Bay of Biscay (Atlantic Ocean) and the Gulf of Lions (Mediterranean Sea). Although average concentrations and the trace element pollution index were generally higher in the Gulf of Lions, significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
(71 reference statements)
1
16
3
Order By: Relevance
“…Gobert et al, 2017), while for other species, no dependency is found (e.g. Mille et al, 2018). The absence of relationship likely indicates that fish regulate some TE at a certain concentration required for efficient metabolic activities (Canli and Atli, 2003;Hornung et al, 1993).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Gobert et al, 2017), while for other species, no dependency is found (e.g. Mille et al, 2018). The absence of relationship likely indicates that fish regulate some TE at a certain concentration required for efficient metabolic activities (Canli and Atli, 2003;Hornung et al, 1993).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, although several studies have already been conducted on TE in Mediterranean fish (e.g. Canli and Atli, 2003;Iamiceli et al, 2015;Mille et al, 2018), some elements such as Al, Ti and V have rarely been investigated (Eisler, 2010). Lastly, the present study provides a baseline dataset for various…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Trace metals, such as iron (Fe), zinc (Zn), copper (Cu), cobalt (Co), manganese (Mn), nickel (Ni), chromium (Cr), or selenium (S), are essential elements that are involved in the normal metabolism of fish [ 2 ]. Other trace metals, such as lead (Pb) and cadmium (Cd) are non-essential elements and do not have any biological role in the fish’s organism [ 21 ]. Both essential and non-essential metals may become toxic above a specific threshold [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other trace metals, such as lead (Pb) and cadmium (Cd) are non-essential elements and do not have any biological role in the fish’s organism [ 21 ]. Both essential and non-essential metals may become toxic above a specific threshold [ 21 ]. Furthermore, alkali metals, such as sodium (Na) or potassium (K), and alkaline earth metals, such as calcium (Ca) or magnesium (Mg), influence the bioaccumulation capacity of trace metals in fish [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation